Needs Analysis for the Development of Electronic Story Calender Media to Improve Spirit of Nationalism - Ambarsari, Ria; Sartono, E Kus Eddy; Mustadi, Ali; Zubaidah, Enny; Jhon, Winarni; Rafsanzani, Muhammad Akbar (Journal of Education Research and Evaluation, 2021)
This study aimed to identify and analyze instructional media that need to be developed and optimized for fifth-grade students in Elementary School in Seberang Ulu 2 districts in Palembang. This research implemented a mixed-method design with a qualitative and quantitative approach and the explanatory model. We distributed a questionnaire towards 121 students through Google Forms and also interviewed nine teachers and nine students. We found that: (1) regarding needs for the development instructional media to improve reading comprehension skills, 45% teachers agreed that it was very necessary and 64% students agreed that it was necessary, (2) regarding interest towards electronic story calendar media, 56% teachers agreed that it was interesting and 49% students agreed that it was very interesting, and (3) regarding needs for the development of electronic story calendar media about the national hero, 56% teachers agreed that it was very necessary and 50% students agreed that it was necessary.